2020
DOI: 10.30935/cedtech/7949
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 the Gateway for Digital Learning in Mathematics Education?

Abstract: Digital learning has reshaped education in many ways. The purpose of this study is to respond to the question of whether COVID-19 is the gateway for digital-learning in mathematics education. To this end, this study explores some uptakes of social media platforms by prospective secondary school teachers. Data was collected from 102 prospective mathematics teachers from the Copperbelt University (CBU). Cluster analysis approach was used. Results revealed that participants' scores for digital learning in mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
180
1
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(210 citation statements)
references
References 12 publications
9
180
1
20
Order By: Relevance
“…The current study showed that the most popular device that students used to access the online materials was the smart phone followed by laptop, while the least used tool was the personal computer. This result is in accordance with the results reporting that students use smart phones and laptops at higher rates followed by iPads/tablets then PC to access online mathematics lessons ( 26 ) and social media ( 27 ). In this regard, Lazarus et al ( 28 ) showed that the use of mobile devices in studying anatomy among medical students in South Africa has a positive impact on students' learning experience.…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that the most popular device that students used to access the online materials was the smart phone followed by laptop, while the least used tool was the personal computer. This result is in accordance with the results reporting that students use smart phones and laptops at higher rates followed by iPads/tablets then PC to access online mathematics lessons ( 26 ) and social media ( 27 ). In this regard, Lazarus et al ( 28 ) showed that the use of mobile devices in studying anatomy among medical students in South Africa has a positive impact on students' learning experience.…”
Section: Discussionsupporting
confidence: 92%
“…Many educational institutions globally are currently adopting new strategies for teaching and learning as various digital online platforms are being adopted to replace the physical classroom since schools are under lock and key (Mulenga & Marbán, 2020). The results of this study specify that COVID-19 will have a negative impact on the education system in Nigeria, due to the effect of lost in contact hours as a result of early closure of schools across the Nation.…”
Section: Discussionmentioning
confidence: 84%
“…In the field of mathematical modeling, many experts predict when the pandemic reaches its peak when it ends, and the transmission model of the spread of viruses (Kim et al, 2020;Ndaïrou et al, 2020;Nuraini et al, 2020;Peirlinck et al, 2020;Rahimi & Abadi, 2020;Resmawan & Yahya, 2020;Soewono, 2020;Tang et al, 2020). Whereas in learning mathematics in schools, research on obstacles in the use of e-learning that occurred in schools (Mailizar et al, 2020;Mulenga & Marbán, 2020).…”
Section: Introductionmentioning
confidence: 99%